Adiabatic Quantum Dynamics of CH(X2?)+H(2S) Reactions on the CH2((X)over-tilde3A) Surface and Role of the Excited Electronic States - Gamallo, P.; Defazio, P.; Akpinar, S.; Petrongolo, C. (Amer Chemical Soc, 2012)
We present the Born-Oppenheimer (BO) quantum mechanical (QM) dynamics of the CH decay (d) CH(X-2 Pi) + H(S-2) -> C(P-3) + H-2(X-1 Sigma(+)(g)) and of the H exchange reaction (e) CH(X-2 Pi) + H'(S-2) -> CH'(X-2 Pi) + H(S-2) on the CH2 (X) over tilde (3)A '' adiabatic potential energy surface (PES) of Harding et al. (J. Phys. Chem. 1993, 97, 5472). A thorough analysis of the correlation diagram of the four lowest CH2 electronic states, as well as Renner-Teller and spin-orbit nonadiabatic test calculations on the (X) over tilde (3)A '', (a) over tilde (1)A', and (b) over tilde (1)A '' coupled PESs, validate the (X) over tilde (3)A '' BO results, confirming that these reactions occur essentially on the uncoupled (X) over tilde (3)A '' ground surface. We consider the CH molecule in the ground vibrational state and in the four lowest rotational states j(0). Thus, we obtain initial-state resolved reaction probabilities, cross sections, and rate constants by propagating coupled-channel real wave packets and performing flux analyses. If J is the total angular momentum quantum number and K is its projection along the body-fixed z axis, CH + H gives essentially the C + H-2 products via a barrierless K-inhibited insertion, CH2 resonances at low J, and large cross sections near the threshold. These cross sections decrease strongly with collision energy and depend slightly on j(0). On the other hand, the small cross sections obtained for the (e) channel are nearly independent of energy. From initial-state resolved rate constants and Boltzmann populations at temperature T, we obtain QM thermal rate constants from 100 to 400 K: at 300 K, k(d) = (9.57 +/- 0.96) x 10(-11) and k(c) = (1.41 +/- 0.14) x 10(-11) cm(3) s(-1) (d) and (e) reactions, respectively. The k(d) value is in good agreement with previous quasi-classical trajectory (QCT) results on the same PES, but it is larger than that observed at 297 K by a factor of similar to 7. On the contrary, and in agreement with the small role of CH2 excited electronic states, (X) over tilde (3)A '' QCT and experimental rate constants agree at high temperatures. Thus, the discrepancy obtained at room T between theory and experiment should be due to an experimental error or to some theoretical effects that we have not been considered in this work. At the present state of the art, an experimental error is more likely and suggests a new measurement of the rate constant.
Keywords: Potential-Energy Surface; Ground-State